Nonpharmacological Interventions for Cancer‐Related Fatigue: A Systematic Review and Bayesian Network Meta‐Analysis. Issue 2 (28th March 2019) - Wu, Chunxiao; Zheng, Yan; Duan, Yuting; Lai, Xin; Cui, Shaoyang; Xu, Nenggui; Tang, Chunzhi; Lu, Liming
Abstract: Background: Nonpharmacological interventions are the first recommendation for cancer‐related fatigue, according to current guidelines. There are many forms of nonpharmacological interventions for addressing cancer‐related fatigue, but the preferred means remain controversial and are not stated in the guidelines. Therefore, we evaluated the comparative effects and ranks of all major nonpharmacological interventions, according to different assessment methods, in cancer patients with fatigue. Methods: Medline, Embase, Cochrane Library, and Allied and Complementary Medicine Database were searched for randomized controlled trials on nonpharmacological treatments for cancer‐related fatigue. We assessed the trials' methodological quality using the Cochrane Risk of Bias tool. A Bayesian network meta‐analysis and a comparative effects ranking were performed with Aggregate Data Drug Information System software. Results: A total of 16, 675 items were obtained from the databases, and 182 studies comprising 18, 491 participants were included in the analysis. Based on the ranking probabilities, multimodal therapy and qigong ranked best with a Brief Fatigue Inventory; for a Functional Assessment of Cancer Therapy‐fatigue scale, combined psychosocial therapies and bright white light therapy ranked best; for the Piper Fatigue Scale, resistance exercise and mindfulness‐based stress reduction ranked best; for a multidimensional fatigue inventory, multimodal therapy and cognitive behavioral therapy (CBT) ranked best; for the European Organization for Research and Treatment of Cancer Quality of Life Questionnaire (EORTC QLQ‐C30), acupuncture and CBT ranked best; and for the Profile of Mood States Fatigue Subscale, multimodal therapy, qigong, aerobic exercise, and CBT ranked best. Comprehensive analysis of the results indicated that multimodal therapy, CBT, and qigong might be the optimum selections for reducing cancer‐related fatigue. Most of the included studies had low risk of methodological quality problems; however, 59 studies had low methodological quality. Linking Evidence to Action: Different interventions have their own sets of advantages for addressing cancer‐related fatigue. These results can be utilized as evidence‐based interventions for healthcare workers and patients to manage cancer‐related fatigue.